Parental Cognitions About Sleep Problems in Infants: A Systematic Review - Knappe, Susanne; Pfarr, Anna-Lisa; Petzoldt, Johanna; Härtling, Samia; Martini, Julia (Frontiers in Psychiatry, 2020)
Introduction: Parental cognitions may directly and indirectly contribute to infant sleep outcomes. This review provides a systematic up-to-date overview of the associations between parental cognitions and infant sleep problems with special emphasis on temporal relationships and the content of parental cognitions. Methods: A systematic literature research in PubMed and Web of Science Core Collection sensu Liberati and PRISMA guidelines was carried out in March 2020 using the search terms (parent* AND infant* AND sleep* problem*), including studies with correlational or control group designs investigating associations between parental cognitions and sleep problems in children aged 1–6 years. Results: Twenty-three studies (published from 1985 to 2016) met inclusion criteria, of which 14 reported group differences or associations between parental sleep-related cognitions and child sleep outcomes. Nine papers additionally reported on the role of general parental child-related cognitions not directly pertaining to sleep. Findings from longitudinal studies suggest that parental cognitions often preceded child sleep problems. Cognitions pertaining to difficulties with limit-setting were especially prevalent in parents of poor sleepers and were positively associated with both subjective and objective measures of child sleep outcomes. Conclusions: Parental cognitions appear to play a pivotal role for the development and maintenance of sleep problems in young children, arguing that parents' attitudes and beliefs regarding child sleep inadvertently prompts parental behavior toward adverse sleep in offspring. Associations are however based on maternal reports and small to moderate effect sizes. Thus, additional parental factors such as mental health or self-efficacy, as well as additional offspring factors including temperamental dispositions and regulatory abilities, require consideration in further studies.